Problematika Pembelajaran Pendidikan Agama Islam di SMA Muhammadiyah Imogiri Bantul - Sujadi (Fakultas Agama Islam, 2015)
Problematika Pembelajaran Pendidikan Agama Islam di SMA Muhammadiyah Imogiri Bantul